MODEL PARTISIPASI MASYARAKAT DALAM PENENTUAN KEBIJAKAN PARIWISATA HALAL DI MADURA BERBASIS NILAI KEISLAMAN DAN HUKUM POSITIF - Achmad Badarus Syamsi; Adiyono Adiyono (istinbath, 2020)
Madura Island has its own uniqueness from a socio-culture that breathes Islam. This is a positive value in dealing with halal tourism in the world. The fact that currently all districts in Madura have not welcomed halal tourism as a mainstay to increase the number of tourist visits both domestic and foreign. This can occur because public participation in policy making is still lacking or even non-existent. Because seeing the very strong diversity of the Madurese community with Islam, it is a must to implement a halal tourism policy. Public participation in drafting local regulations on tourism management in Madura can be seen in the FGD. This shows that the model of community participation in Madura is in accordance with a basic model of public participation, and a realism model of public participation. Meanwhile, based on Islamic values, the implementation of FGD can be included in the shura concept contained in Islam. The general public response wants the application of halal tourism on the island of Madura. But on the other hand they also emphasize the existence of halal tourism which actually implements tourism in accordance with the Shari’a.